The Influence of Parental Involvement on Academic Achievement: A Comparative Study Across Different Educational Systems - Riky Supratama (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This study employs a qualitative comparative case study design to explore the influence of parental involvement on students' academic achievement across different educational systems. By examining how parental involvement is perceived and practiced in various contexts, the research aims to understand the impact of these variations on students' academic outcomes. Participants, including parents, teachers, and students, were selected through purposive sampling to represent diverse educational systems. Data were collected through in-depth interviews, focus group discussions, observations, and document analysis. Thematic analysis revealed key themes related to the nature of parental involvement, perceptions of parental roles, and the impact on academic achievement. Comparative analysis across different educational systems highlighted both similarities and differences in parental involvement practices, influenced by cultural attitudes and institutional policies. The findings suggest that robust parental involvement, supported by effective policies and resources, positively impacts students' academic performance. The study's implications extend to educational policy, emphasizing the need for culturally responsive and inclusive approaches to enhance parental engagement in diverse educational contexts.